Phosphotyrosine profiling identifies ephrin receptor A2 as a potential therapeutic target in esophageal squamous‐cell carcinoma. Issue 2 (January 2015) - Syed, Nazia; Barbhuiya, Mustafa A.; Pinto, Sneha M.; Nirujogi, Raja Sekhar; Renuse, Santosh; Datta, Keshava K.; Khan, Aafaque Ahmad; Srikumar, Kotteazeth; Prasad, T. S. Keshava; Kumar, M. Vijaya; Kumar, Rekha Vijay; Chatterjee, Aditi; et al.
<x xml:space="preserve">Abstract</x> Esophageal squamous‐cell carcinoma (ESCC) is one of the most common malignancies in Asia. Currently, surgical resection of early‐stage tumor is the best available treatment. However, most patients present late when surgery is not an option. Data suggest that chemotherapy regimens are inadequate for clinical management of advanced cancer. Targeted therapy has emerged as one of the most promising approaches to treat several malignancies. A prerequisite for developing targeted therapy is prior knowledge of proteins and pathways that drive proliferation in malignancies. We carried out phosphotyrosine profiling across four different ESCC cell lines and compared it to non‐neoplastic Het‐1A cell line to identify activated tyrosine kinase signaling pathways in ESCC. A total of 278 unique phosphopeptides were identified across these cell lines. This included several tyrosine kinases and their substrates that were hyperphosphorylated in ESCC. Ephrin receptor A2 (EPHA2), a receptor tyrosine kinase, was hyperphosphorylated in all the ESCC cell lines used in the study. EPHA2 is reported to be oncogenic in several cancers and is also known to promote metastasis. Immunohistochemistry‐based studies have revealed EPHA2 is overexpressed in nearly 50% of ESCC. We demonstrated EPHA2 as a potential therapeutic target in ESCC by carrying out siRNA‐based knockdown studies. Knockdown of EPHA2 in ESCC cell line TE8 resulted in significant decrease in cell proliferation and invasion, suggesting it is a promising therapeutic target in ESCC that warrants further evaluation.